Cardiac arrhythmias and conduction disorders monitoring after transcatheter aortic valve replacement procedure, using a mobile electrocardiogram 6 lead device. (3rd October 2022) - De Lucia, R; Giannini, C; Parollo, M; Costa, G; Barletta, V; Giannotti Santoro, M; Primerano, C; De Carlo, M; Angelillis, M; Zucchelli, G; Petronio, A S
Abstract: Background: In the early post transcatheter aortic valve replacement (TAVR) discharge era, rate of readmission for permanent pacemaker implantation (PPM-I) due to delayed conduction disturbances (CDs) has significantly increased. This issue has powered post procedural ambulatory electrocardiogram (AECG) monitoring by using implantable cardiac monitors or mobile cardiac telemetry devices, despite several disadvantages as frequent electrode changes and costs. Purpose: In this scenario we aimed to evaluate the incidence of post-TAVR new onset arrhythmias and delayed CDs, performing an AECG monitoring through a 30s spot digital ECG (AeECG), by using a mobile electrocardiogram 6 lead (ME6L) device in a 30 days period after a TAVR procedure. Methods: Between March 2021 and February 2022 we consecutively enrolled all patients undergoing a TAVR at the University Hospital of Pisa, excepting who already had a PM. At discharge, all patients received ME6L device and were asked to record a spot eECG for 1 month: 1 eECG per day during the first week and then 1 eECG per week. Clinical and follow-up data were collected and analyzed, and eECG scheduling compliance and quality recordings were explored. Results: Among 185 consecutive TAVR patients, 12 were excluded due to pre-existing pacing device and 33 due to PPM-I <2 days post TAVR; 3 died before enrollment and 10 refused the enrollment; 18 were excluded because failed the ME6L training phase, 6 for severe postprocedural complications and the last 3 because affected by isolated aortic regurgitation.The remaining ones (100) had 30-day AeECG data. Delayed CDs with a Class I/IIa indications for PPM-Ioccurred in 8 patients with a median of 6 days (range 4–8 days) post-TAVR. New onset documented arrhythmias were AT/AF in 3 patients, isolated PVCs in 10 patients, and competitive transitory junctional rhythm in 2 patients. Delayed PPM-I versus non-delayed PPM-Ipatients were more likely to have a non-self-expandable valve (3 vs 69; p=0.02) and longer PR and QRS intervals at discharge (250.00±53, 29 ms vs 179.17±39.17 ms; p=0, 003; 125±33.38 ms vs 102.55±30.48 ms; p=0, 04). The overall eECG schedule level compliance was 96.5%. Out of a total of 965 sent eECGs, 950 (98, 4%) have been correctly recorded and transmitted. Conclusion: Delayed CDs requiring PPM-I are the most important drawback of TAVR procedure. In our study, AeECG was seen to be safe and helpful in the identification and treatment of delayed CDs requiring PPM-I, with a very high eECG schedule level of compliance and quality. Further prospective studies are needed to better identify patient selection for outpatient monitoring, making safer and safer the early post TAVR discharge approach. Funding Acknowledgement: Type of funding sources: None.